THE EFFECT OF HEALTH EDUCATION WITH TB CARD ON THE PREVENTION OF PULMONARY TB TRANSMISSION BEHAVIOR - Wiliyanarti, Pipit Festi; Putra, Kusuma Wijaya Ridi; Annisa, Faida (University of Muhammadiyah Malang, 2020)
ABSTRACT Introduction: The high prevalence caused by pulmonary TB disease results in an increased risk of transmission to the family. Health education at the Medoan Ayu puskesmas was carried out in an integrated manner with various programs but the results are less than optimal. Objective: the research objective is to find out the effect of health education with the TB Card media on the prevention of pulmonary TB transmission behavior in families at the Medoan Ayu Puskesmas Surabaya. Method: Pre-experimental one group pre-post test design. The population was 34 and the sample is 30 TB patients with non probability purposive sampling technique. The research variables consisted of independent variables, health education with TB Card media and the dependent variable, behavioral prevention of pulmonary TB transmission. The instrument used was a questionnaire sheet, analysis used the Wilcoxon Signed Rank Test statistical test. Result: The results of the study before getting the intervention obtained less behavior of 12 respondents (40%), enough behavior of 12 respondents (40%), the results of the study after getting the intervention obtained good prevention behavior 26 (87%) and the results of the statistical test the influence of TB media on prevention practices p = 0,000 <a = 0.05, there is an effect of health education with TB Card Media on the prevention of pulmonary TB transmission behavior in families in the Medoan Ayu Puskesmas area of Surabaya. Discussion: Behavior to prevent TB transmission in the family needs to be increased so as to reduce the morbidity caused by pulmonary TB disease.